2021
DOI: 10.3389/fimmu.2021.730746
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Infiltrating B- and T-Cell Repertoire in Pancreatic Cancer Associated With Host and Tumor Features

Abstract: BackgroundInfiltrating B and T cells have been observed in several tumor tissues, including pancreatic ductal adenocarcinoma (PDAC). The majority known PDAC risk factors point to a chronic inflammatory process leading to different forms of immunological infiltration. Understanding pancreatic tumor infiltration may lead to improved knowledge of this devastating disease.MethodsWe extracted the immunoglobulins (IGs) and T cell receptors (TCRs) from RNA-sequencing of 144 PDAC from TCGA and 180 pancreatic normal ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…In addition, immune in ltration also signi cantly affects the development of cancer (30). Pancreatic cancer has been con rmed to be closely related to the in ltration of T cells and B lymphocytes in immune cells (31) and is signi cantly higher than normal pancreatic tissue, which is consistent with our research results. pancreatic cancer tissue has a high level of in ltration of CD8T cells, regulatory T cells, B cells, and other immune cells (32).…”
Section: Discussionsupporting
confidence: 90%
“…In addition, immune in ltration also signi cantly affects the development of cancer (30). Pancreatic cancer has been con rmed to be closely related to the in ltration of T cells and B lymphocytes in immune cells (31) and is signi cantly higher than normal pancreatic tissue, which is consistent with our research results. pancreatic cancer tissue has a high level of in ltration of CD8T cells, regulatory T cells, B cells, and other immune cells (32).…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, using a genetic animal model, Lee et al demonstrated accumulation of HIF-1α in early pancreatic neoplasia but HIF-1α deletion accelerates PDAC initiation by increasing B cell infiltration, suggesting the pro-neoplastic effect of B cells ( 79 ). However, the role of B cells in anti-tumor immunity is still controversial ( 80 , 81 ). Therefore, further studies are needed to clarify the role of B cell immunity in human PDAC and its interaction with HIF-1.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies [42,43], the smoking history has been associated with higher tumor-infiltrating immune cells in breast and lung cancer patients. In PDAC, Pineda et al [44] showed that smoking might increase the incidence of somatic mutations, generate neoantigens, and cause an amplified immunogenicity. Antitumor immune responses induced by smoking might promote TLS development in PDAC.…”
Section: Discussionmentioning
confidence: 99%